Analysis of the Influence of Knowledge Levels and Public Perceptions on the Decision to Choose Murabaha Financing at Islamic Banks - Shofiyul Umam (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
This study aims to analyze the influence of the level of knowledge about murabahah financing (X1) and perception of murabahah financing (X2) on the decision to choose murabahah financing (Y) among the community in Surabaya. The research employs a quantitative approach with descriptive analysis. Sampling technique using the Slovin formula yielded a sample size of 400 individuals from the Surabaya community. Data collection was conducted through questionnaires and analyzed using data quality tests, classical assumption tests, hypothesis testing, and multiple linear regression analysis. The results indicate that both the level of knowledge about murabahah financing and the perception of murabahah financing have a positive and significant effect, both partially and simultaneously, on the decision to choose murabahah financing among the community in Surabaya.